EVOLUTION SCENARIO OF ? CAPRICORNI BINARY STAR SYSTEM - Aulia Salima, Fitrin
A binary star is a star system in which two stars interact gravitationally and orbit each other. The evolution experienced by each star in a multiple star system is different from the evolution of a single star because of the influence of its partner star. The ? Capricorni binary star system is one of the Short Period Non Contact (SPNC) binary star systems that has a period of ? 1 day. This final project discusses evolutionary scenarios that may occur in the ? Capricorni binary star system with components that are in the main sequence phase in the Hertzsprung-Russel diagram. The conclusions obtained from this study are expected to add insight regarding the evolution scenario of the SPNC binary star system. There are two evolutionary scenarios that have different combinations of masses of the two stars, but have the same mass ratio (q = M2/M1) which is q = 0.365. Evolutionary modeling was carried out using the Modules for Experiment in Stellar Astrophysics (MESA) software. Both evolutionary scenarios suggest that the ? Capricorni binary star system will undergo mass transfer from one component to another. The difference between the two evolutionary scenarios discussed in this study is the position of the primary components in the Hertzsprung-Russel diagram when mass transfer begins. To determine the most suitable evolutionary scenario, further observations need to be made by examining changes in the period of the ? Capricorni star system through O-C analysis to obtain the most suitable mass combination.